Does waste make language?. (2nd April 2022) - Reno, Joshua
Abstract: In Thurlow's (2022) paper in this journal, he offers an innovative approach to combining discard studies and sociolinguistics. Many of the examples are about language creating waste in different ways. In this response, I explore the opposite possibility—that is, how waste could be said to create language in turn. I do so with specific attention to how sociolinguistics can be approached through what cannot be said (taboo) and who cannot speak. As examples, I compare two seemingly unrelated yet similarly controversial and important scandals in late 20th century New York State: the pollution caused by the closed yet undisclosed landfill in Love Canal and the abuse and neglect of disabled persons at Willowbrook State School. These are not normal subjects for sociolinguistics, and the latter is not a normal one in discard studies either. Yet I argue that taking them together helps create unexpected linkages between these fields. In doing so, I argue that taking into account what goes unsaid and who cannot speak also helps reveal some of the undiscussed politics in both discard studies and sociolinguistics alike.